Beyond Menopause - Navigating Holistic Approach in Managing Dry Eyes (Asian Journal of Pharmaceutics (AJP), 2024)
Among all ocular conditions, dry eye remains one of the most prevalent in clinical practice, ranging from 5% to50% with higher variations in signs than symptoms. Increased age, female sex, and Asian ethnicity are amongthe most consistent risk factors for developing dry eye disease. The prevalence of dry eye increased by 14.4%in people aged 48–91, with the prevalence of the disorder more than doubling after the age of 59. Females aremore prone to develop dryness, especially in the post-menopausal age group. Sex hormones play a key role inmaintaining the homeostasis of the tear film. Hence, older women tend to develop dry eyes more than the otherage groups. Considering the clinical features of dry eyes and analyzing the diseases in Ayurveda Netra Roga, thedisease closely resembles the condition Shushkakshipaka Dosha predominance according to Sushruta is vata andVagbhata explains it as vata pitta pradhanavyadhi. Aggravation of vata and pitta dosha leads to the shoshana ofnethragatasneha contributed by kapha dosha. Considering the age and ritunivrutii kala (menopausal age), both aredominated by vata and also the disease. In consideration with the normal dry eyes population, this age group needsspecial consideration in addressing both post-menopausal dry eyes and other menopause-related issues. Hence,this review is planned to establish the correlation between dry eyes and shushkakshipaka to explore a betteralternative treatment for post-menopausal dry eyes, and improve overall health in this population.